KOMPARASI KINERJA PERBANKAN YANG BERBASIS SYARIAH DENGAN PERBANKAN YANG BERBASIS NON SYARIAH (Studi pada Bursa Efek Indonesia) - STIE Lhokseumawe (Sekolah Tinggi Ilmu Ekonomi Lhokseumawe, 2020)
This study aims to determine the comparison and differences in the performance of Sharia- Based Banks with Non-Sharia-Based Banks that were listed on the Indonesia Stock Exchange in 2016-2018. The data used in this study are secondary time series data. Data analysis methods are financial ratio analysis, comparison test and two average difference test (Independent Sample T-Test) with the help of SPSS program. The results of the study show that: Comparison of banking performance shows that Non Sharia Based Banking has CAR, NIM, ROA and BOPO better than Sharia Based Banking. Whereas Sharia-Based Banking has a better LDR than Non-Sharia-Based Banking. The average two different test results indicate that there is no significant difference in the performance of Sharia-Based Banking and Non-Sharia-Based Banking from CAR and NIM ratios. While the ROA, BOPO and LDR ratios are significant differences between the performance of Sharia-Based Banking and Non-Sharia-Based Banking performance.